Additive manufacturing in bone science: A cutting-edge review of its potential and progress - Md Shakil Chowdhury; Md Shah Oliullah; Md Zisat Hossen; Mehedi Hasan Manik; MD Abu Hurayra; Md. Zobair Al Mahmud; Nayem Hossain; Md Hosne Mobarak; Md Didarul Islam (Medicine in Novel Technology and Devices, 2025)
In the medical industry, additive manufacturing, or AM, sometimes referred to as 3D printing, has completely changed bone regeneration and healing. With the use of this technology, complex scaffolds and implants that nearly resemble natural bone structures may be created. Orthopedic patient-specific solutions may be created by utilizing a variety of AM processes, including as fused deposition modeling, stereolithography, and selective laser sintering. Compared to conventional bone grafting techniques, AM lowers risks while promoting cellular development, differentiation, and osseointegration. When bioactive chemicals are used with biocompatible materials like metals, ceramics, and polymers, bone tissue engineering becomes even more effective. The potential of AM in bone regeneration is reviewed in this research along with an analysis of its uses, benefits, and new materials. Issues including material constraints, expenses, and regulatory issues are discussed, and suggestions for more study are included. AM has the potential to significantly improve clinical procedures and patient outcomes by revolutionizing the fields of bone tissue engineering and orthopedic implants.